Panduan Konseling dengan Teknik Coping Self-Talk untuk Mengatasi Body Dysmorphic Disorder Siswa Sekolah Menengah Kejuruan - Fikriyah, Aidatul; Simon, Irene Maya; Lasan, Blasius Boli (Buletin Konseling Inovatif, 2021)
This research and development aim to create a counseling guideline with coping self-talk technique to resolve vocational high school students' body dysmorphic disorder. It used a research and development model from Borg and Gall. The results of the assessment carried out by experts and field assessment on the user candidate were analyzed using the inter-rater agreement model. The validity index of the experts and users demonstrates very high criteria. This counseling guideline has followed the requirements from the National Education Standard Institution and four acceptability aspects so that it is feasible to be used.